Enhancing the Performance of Perovskite Light-Emitting Diodes via Synergistic Effect of Defect Passivation and Dielectric Screening - Yu, Xuanchi; Guo, Jia; Mao, Yulin; Shan, Chengwei; Tian, Fengshou; Meng, Bingheng; Wang, Zhaojin; Zhang, Tianqi; Kyaw, Aung Ko Ko; Chen, Shuming; Sun, Xiaowei; Wang, Kai; et al. (Nano-Micro Letters, 2024)
Metal halide perovskites, particularly the quasi-two-dimensional perovskite subclass, have exhibited considerable potential for next-generation electroluminescent materials for lighting and display. Nevertheless, the presence of defects within these perovskites has a substantial influence on the emission efficiency and durability of the devices. In this study, we revealed a synergistic passivation mechanism on perovskite films by using a dual-functional compound of potassium bromide. The dual functional potassium bromide on the one hand can passivate the defects of halide vacancies with bromine anions and, on the other hand, can screen the charged defects at the grain boundaries with potassium cations. This approach effectively reduces the probability of carriers quenching resulting from charged defects capture and consequently enhances the radiative recombination efficiency of perovskite thin films, leading to a significant enhancement of photoluminescence quantum yield to near-unity values (95%). Meanwhile, the potassium bromide treatment promoted the growth of homogeneous and smooth film, facilitating the charge carrier injection in the devices. Consequently, the perovskite light-emitting diodes based on this strategy achieve a maximum external quantum efficiency of 21% and maximum luminance of 60,000 cd m−2. This work provides a deeper insight into the passivation mechanism of ionic compound additives in perovskite with the solution method. Highlights: 1 Synergistic passivation mechanism of the dual functional compound of potassium bromide for metal halide perovskite films, that is through chemical bonding and physical screening towards the various types of defects. 2 Metal-ion additives can simultaneously passivate the defects of halide vacancies with bromine anions and dangling bond defects with metal cations. 3 Achieve the maximum external quantum efficiency of 21% and maximum luminance of 60,000 cd m−2.